Association of Human Papilloma Virus Infection and Oral Squamous Cell Carcinoma in Bangladesh - Akhter, Mahmuda; Ali, Liaquat; Hassan, Zahid; Khan, Imran (Journal of Health, Population and Nutrition, 2013)
Oral squamous cell carcinoma is the sixth most common malignancy worldwide. In Bangladesh, it comprises 20% of the whole body malignancies. Several studies found that 15% to 25% of oropharyngeal cancer cases are associated with human papilloma virus (HPV). This study is done to find the association of human papilloma virus subtypes, particularly HPV type 16 and HPV type 18, with the oral squamous cell carcinoma in Bangladeshi patients. In total, 34 diagnosed patients of oral squamous cell carcinoma were included in the study. Extracted DNA from the cancerous tissues was checked for PCR reaction to detect the subtypes of human papilloma virus. Data of the present study suggest that oral squamous cell carcinoma are almost absent in Bangladeshi patients with human papilloma virus, particularly HPV 16 and 18. J HEALTH POPUL NUTR 2013 Mar;31(1):65-69 DOI: http://dx.doi.org/10.3329/jhpn.v31i1.14750